Modelling the large earthquakes recurrence times along the North Aegean Trough Fault Zone (Greece) with a physics-based simulator. Issue 3 (1st March 2021) - Kourouklas, Christos; Console, Rodolfo; Papadimitriou, Eleftheria; Murru, Maura; Karakostas, Vassilios
SUMMARY: The recurrence time of large earthquakes above a predefined magnitude threshold on specific faults or fault segments is one of the key parameters for the development of long-term Earthquake Rupture Forecast models. Observational data of successive large earthquakes per fault segment are often limited and thus inadequate for the construction of robust statistical models. The physics-based earthquake simulators are a powerful tool to overcome recurrence data limitations by generating long earthquake records. A physics-based simulator, embodying well known physical processes, is applied in the North Aegean Trough (NAT) Fault Zone (Greece). The application of the simulation is implemented, after defining a five segment source model, aiming at the investigation of the recurrence behaviour of earthquakes with M w ≥ 6.5 and M w ≥ 7.0. The detailed examination of the 544 M w ≥ 6.5 earthquakes included in the simulated catalogue reveals that both single and multiple segmented ruptures can be realized along the NAT. Results of statistical analysis of the interevent times of M w ≥ 6.5 and M w ≥ 7.0 earthquakes per participating segment to the related ruptures indicate the better performance of the Brownian Passage Time renewal model in comparison to exponential model. These results provide evidence for quasi-periodic recurrence behaviour, agreeing with the elastic rebound theory, instead of Poissonian behaviour.